VIDEO UJI KADAR TIMBAL PADA DAUN MAHONI SEBAGAI MEDIA BELAJAR PADA POKOK BAHASAN PENCEMARAN UDARA DI SMA NEGERI 2 KARANGANYAR - Octovi, Chrisnia; Muzayyinah, Muzayyinah; Ariyanto, Joko (Pendidikan Biologi, 2011)
ABSTRACT ? This research aims was  to find out  the use of video as media learning toward the students  achievement of the class X at SMA Negeri 2 Karanganyar.  This  study was a quasi-experimental studies which use Randomized Control-Group Only Design. The independent variable  in this research is video as media learning and the dependent variable  was biology students? achievement. The population of the study was the entire students of X second semester classes SMA Negeri 2 Karanganyar 2010/2011 school year. The sample of the study was  the students of X.6 class as the control group and the students of X.5 class as the experiment group.  The sample  was  taken by using Cluster Random Sampling method. The  data are collected by using test for cognitive achievement and the observation methods was used to find out the  learning effectivity and psychomotor domain. The technique of  data analysis by using t-test. The result shows the use of video as media learning was significantly influences the students? achievement in cognitive and psychomotor aspect, but did not give effects improve the affective  achievement  of class X  at  SMA Negeri 2 Karanganyar Keywords: Media, Video Learning, Learning Achievement, The Air Pollution.